68Ga-DOTA-TATE—a source of eye lens exposure for nuclear medicine department workers. (23rd November 2018) - Wrzesień, M; Albiniak, Ł
Abstract: Introduction. Obtaining 68 Ga-DOTA-TATE (a radioconjugate consisting of the somatostatin analogue tyrosine-3-octreotate (Tyr3-octreotate or TATE) labelled with the positron emission tomography tracer gallium 68 Ga via the macrocyclic chelating agent dodecanetetraacetic acid (DOTA)) is a complex process and, as with any radiopharmaceutical whose basis is a short-lived radionuclide generator, it is based on a sequence of procedures beginning from the 68 Ge/ 68 Ga generator elution, labelling ligands with a radioisotope, dispensing doses of 68 Ga-DOTA-TATE for patients and finally injection of the preparation to patients. The complexity of this process may contribute to an increased exposure of eye lenses of the staff who perform the above-mentioned procedures, which is especially important at a time when the dose limit on the lens of the eye is being reduced from 150 to 20 mSv yr –1 . Objective. The work presents the exposure of eye lenses of the personnel of a nuclear medicine department who prepare and inject 68 Ga-DOTA-TATE. Materials and methods. Radiochemists and nurses were monitored by dosimetry measurements with thermoluminescent detectors (TLDs). Results. The values of H p (3)/A—normalised personal eye dose equivalent recorded in the group of radiochemists during the procedure of dispensing the doses of 68 Ga-DOTA-TATE for patients exceeded the value of 274 μ Sv/GBq. Conclusions. The estimated annual H p (3) values may exceed 20 mSv, which is particularly important due to the fact that procedures using the 68 Ga radioactivity are only a small part of the daily professional activity of the staff, resulting from the performance of other procedures that require the use of other radioisotopes.